Quasicrystalline and crystalline types of local protein order in capsids of small viruses. (9th June 2017) - Konevtsova, O V; Pimonov, V V; Lorman, V L; Rochal, S B
Abstract: Like metal alloys and micellar systems in soft matter, the viral capsid structures can be of crystalline and quasicrystalline types. We reveal the local quasicrystalline order of proteins in small spherical viral capsids using their nets of dodecahedral type. We show that the structure of some of the viral shells is well described in terms of a chiral pentagonal tiling, whose nodes coincide with centers of mass of protein molecules. The chiral protein packing found in these capsids originates from the pentagonal Penrose tiling (PPT), due to a specific phason reconstruction needed to fit the protein order at the adjacent dodecahedron faces. Via examples of small spherical viral shells and geminate capsid of a Maize Streak virus, we discuss the benefits and shortcomings of the usage of a dodecahedral net in comparison to icosahedral one, which is commonly applied for the modeling of viral shells with a crystalline local order.